Mapping mangrove distributions in Cherating river estuary, Pahang by using remote sensing - Taib, Siti Noor Aifa; Mohamad Suharni, Muhammad Luqman; Shammodin, Muhammad Shaheed; Ahmad, Zuhairi (Universiti Teknologi Malaysia, 2017)
The mangrove at Cherating river estuary are diverse in species diversity and well distributed along the seven kilometer of the riverine swamp. The study on the mangroves cover are needed for coastal development planning and monitoring. Methodology: Combination of unsupervised and supervised classification of Landsat Satellite imageries were used for the study. Findings: A total of 15 mangrove species comprise of exclusive and non-exclusive mangroves species along the Cherating river estuary have been identified. The mangrove species that are distributed in the riverine swamp of Cherating are dominated by Rhizophora species which are Rhizophora apiculata and Rhizophora mucronata. Based on the supervised classification, a total of 26.32 hectares of the mangrove areas have been lost form 1997 to 2016. Significant decline of the mangroves cover is recorded from the year of 2013 to 2016 with the loss of 9.156 hectares mangrove forest with the percentage of 34.76% of mangroves cover decline from 1997 to 2016. Contribution: However, the decline of the mangrove forest covers have affected the tourism activities as mangrove forest serve as the habitats for floras and faunas. Clearance of mangrove forest for development and timbers exploitation have a negative impact on the firefly habitation. Mangroves covers mapping are important for the future monitoring, management and tourism planning in the Cherating river estuary in order to provide the tourism sector with the recent database on the mangroves cover changes. Sustainable development and the environmental approach in the tourism sectors are important in order to protect the mangrove area from any further decline.